Values, Context, and Culture: The Implementation of Culturally Responsive Teaching (CRT) for Innovation in Elementary School Mathematics Teaching Materials - Rahayu Condro Murti; Yeni Rakhmawati; Fery Muhamad Firdaus; Irfan Wahyu Prananto; Anwar Novianto; Yoppy Wahyu Purnomo (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to improve the competence of elementary school teachers under the Bantul Education Office in implementing Culturally Responsive Teaching (CRT) in mathematics through training, mentoring, and the development of culture-based teaching materials to foster inclusive, engaging, and contextually relevant learning environments. The program was conducted through workshops and hands-on practice, during which teachers were trained to develop teaching modules, lesson plans, instructional media, and assessment instruments that integrate educational values, everyday contexts, and local cultural elements. Program evaluation was conducted using observations, interviews, questionnaires, and documentation, and the data were analyzed through descriptive statistics and thematic analysis to examine participants' engagement, understanding, and feedback. The evaluation results indicated that the integration of educational values received the highest average score (4.71), followed by contextual relevance (4.58) and the incorporation of cultural artifacts (4.22). Although teachers demonstrated a high level of consistency in implementing CRT principles, integrating local culture into mathematics instruction remained a major challenge. The greatest barrier identified was the limited availability of contextual and digital teaching materials, with an average difficulty score of 3.28. Nevertheless, teachers demonstrated a strong awareness of and perceived need for CRT in mathematics education, reflected in a high average score of 5.16. These findings suggest that Culturally Responsive Teaching extends beyond a pedagogical approach by providing a transformative framework that connects mathematics learning with students' lived experiences while preserving local cultural heritage. Continuous mentoring and the development of context-based digital teaching resources are therefore essential to support the sustainable implementation of CRT in elementary schools.